Oral Health Status and Anthropometric Conditions among HIV Infected Adolescents on Antiretroviral Therapy in Mozambique - Sales-Peres SHC; Costa AH; Mapengo MA; Yamashita JM; Xavier CN; Sales-Peres A (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2014)
Background: Malnutrition and weight loss are important characteristics in HIV/AIDS patients.The association between this type of pathology and oral health in HIV/AIDS patients maintains unclear in the literature. Objective: The aim of this study was to assess the oral health status and anthropometric conditions in adolescentstreated and non-treated with HIV infection in Maputo-MZ. Design: Cross-sectional analytical study conducted in the Maputo city, Mozambique in 2012. Methods: The random sample was composed of 143 adolescents from 15-19 years of age,attended to at the Medical Center Hospital and Pediatric Unit of Maputo Hospital. The adolescents were divided into two groups: HIV Group (HIVG)-adolescents with AIDS; Control Group (CG)-adolescents without HIV infection. The oral health conditions were collected by means of the DMFT index, the community periodontal index (CPI) and soft tissue, according to the criteria proposed by the World Health Organization (WHO), by a calibrated researcher. Student's t-Test and Spearman correlation were used for statistical analysis (p<0.05). Results: The HIV group presented a higher degree ofdental caries (OR= 5.902; 95%CI=2.859-12.188; p=0.000), a trend to lessperiodontal diseases(OR=1.318; 95%CI=0.662-2.624; p=0.540),higheralterations in the soft tissue (OR=0.216; 95%CI=0.057-0.811; p=0.030) and higher normal BMI (OR=0.498; 95%CI=0.252-0.987; p=0.066) than the CG group. Conclusion: HIV/AIDS patients are at major risk for dental caries or alterations of soft tissue and minor risk for periodontal diseases, even when on antiretroviral therapy.